Praktik Walimatul ‘Urs di Mandailing Natal: Antara Tradisi, Kepatuhan Sosial, dan Perspektif Maqashid Syariah: Walimatul ‘Urs Practices in Mandailing Natal: Between Tradition, Social Obligation, and the Maqasid al-Shariah Perspective - Zuhdi Hasibuan; Raja Ritonga; Asrul Hamid; Andri Muda Nst; Ilham Ramadan Siregar (ISTIDLAL, 2026)
Walimatul ‘Urs in Mandailing Natal constitutes an integral component of local matrimonial traditions; however, its contemporary practice is frequently marked by excessive expenditure and ostentatious display. In many cases, members of the community irrespective of their socioeconomic status experience considerable social pressure to organize elaborate wedding ceremonies in order to conform to prevailing societal expectations. This study seeks to critically examine the incongruity between such extravagant practices of walimatul ‘urs and the normative framework of Maqasid al-Shariah, which underscores the principles of moderation, prudent wealth management, and the prevention of wastefulness (israf) and harm (mafsadah). Employing a qualitative research design, this study investigates the socio-economic implications of lavish walimah practices and evaluates their alignment with the higher objectives of Islamic law. The findings reveal that the excessive implementation of walimatul ‘urs generates adverse consequences, including substantial financial burdens on the families of the bride and groom, as well as psychological distress arising from heightened social expectations. Furthermore, these practices risk undermining the ethical and social objectives envisioned within the Maqasid al-Shariah framework. In light of these findings, this study advocates for a paradigmatic shift in societal attitudes toward the implementation of walimatul ‘urs, emphasizing simplicity, proportionality, and sustainability. Such a transformation is essential to ensure that matrimonial practices remain aligned with the core values of Islamic teachings while simultaneously fostering long-term social and economic well-being